‘Journeying Together’: Challenges Ahead - Devadoss, Josephine Margaret (Asian Horizons, 2025)
Growing internal and external division, a crisis of authority and subsidiarity, gender inequality and ecological degradation, local and global wars, etc., threaten to tear apart not only the world, but also the church in its efforts to be synodal. The article discusses the challenges and ways forward for making the church more synodal in her journey towards a deeper communion, fuller participation, and greater openness to fulfilling the mission of God in the world. A truly synodal church must be free from a fixed, hyper-institutionalised and over-clericalised image of the church and ministry, and focus instead on the shared baptismal vocation of Christ’s kingly, prophetic, and priestly ministries, and embrace an ecclesiology of equal discipleship. It must be transparent and accountable, especially concerning sexual abuse, finances, ecclesiastical management, and governance. A synodal church demands the involvement of the entire people of God, especially young people. The Church has to renew herself under the influence of the Spirit by listening to the Word and the world, and network with non-governmental, governmental, or faith-based organizations to create, sustain, and nourish an alternative community space or environment. A new style of leadership and a new relationship of power and authority have to emerge, promoting teamwork and a collaborative vision rooted in listening, co-responsibility, involvement, service, accompaniment, and empowerment. The synodal church calls for women’s partnership and leadership in all of its ministries, which is a prophetic sign for the human family. In the process of synodal care, the interconnectedness of justice, peace, and the integrity of creation is to be reaffirmed, reemphasized, and celebrated. Mary is the model and mother, icon, and inspiring figure of the synodal church (Cf. LG, 62) and in the synodal pilgrimage of our life.